Rancang Bangun Sistem Informasi Wedding Organizer Pada Nikah Murah Tangerang - Kurnia Widya Lestari (PT Triputra Sejahtera Prima, 2024)
As time went by, technological developments in the business world demanded the perpetrators to be more creative, as did wedding organizers. The news of the many popular wedding organizers and civil rights cases has given some of the candidates to be clients who will use Nikah Murah Tangerang wedding services to be less confident of wedding service providers. Based on the problem, it requires an information system as relevant evidence to the candidates or clients who will use a Nikah Murah Tangerang wedding service that can be used as a transaction tool to order services to the Nikah Murah Tangerang wedding organizer and data management system to facilitate data management to the providers of wedding management. The research methods used are qualitative methods and extreme programming (XP) as software development methods in this research. Data collection techniques are done by observation, interview, and library study. The results of this study include information systems for web-based wedding organizers that provide information, order processes, and data management for wedding organizers.